A covalent organic framework-based nanoagent for H2S-activable phototherapy against colon cancer. Issue 59 (30th June 2021) - Feng, Jie; Ren, Wen-Xiu; Kong, Fei; Dong, Yu-Bin
Abstract : We report a Cu(ii )-porphyrin-derived COF which can be a H2 S triggered nanoagent to achieve collaborative PDT and PTT against colon cancer. Abstract : Herin, we report a Cu(ii )-porphyrin-derived nanoscale COF, which can be triggered by endogenous H2 S via an intracellular sulfidation reaction to generate a metal-free COF-photosensitizer for PDT against H2 S-enriched colon tumors with controllable singlet oxygen release; meanwhile in situ generated CuS can be synchronously used as a photothermal agent for PTT.